1988
DOI: 10.1051/agro:19880406
|View full text |Cite
|
Sign up to set email alerts
|

Influence d'apports de matière organique sur la culture de mil et d'arachide sur un sol sableux du Nord-Sénégal. I. — Bilans de consommation, production et développement racinaire

Abstract: RÉSUMÉ

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…2) Within any given year, although yield responds strongly to a wide range of management options, ET is relatively conservative. Not surprisingly, therefore, it has been difficult to predict pearl millet yield from ET in West Africa, e.g., in Senegal (Cissé and Vachaud, 1988) and Niger (Klaij and Vachaud, 1992) The lack of a linear relation contrasts yield/ET data of many dense canopied crops, for example, those of grain sorghum [ Sorghum bicolor (L.) Moench] (Stewart, 1989) and maize ( Zea mays L.) (Hanks, 1983)…”
Section: Yield‐et Relations Of Pearl Milletmentioning
confidence: 99%
See 2 more Smart Citations
“…2) Within any given year, although yield responds strongly to a wide range of management options, ET is relatively conservative. Not surprisingly, therefore, it has been difficult to predict pearl millet yield from ET in West Africa, e.g., in Senegal (Cissé and Vachaud, 1988) and Niger (Klaij and Vachaud, 1992) The lack of a linear relation contrasts yield/ET data of many dense canopied crops, for example, those of grain sorghum [ Sorghum bicolor (L.) Moench] (Stewart, 1989) and maize ( Zea mays L.) (Hanks, 1983)…”
Section: Yield‐et Relations Of Pearl Milletmentioning
confidence: 99%
“…Many studies in West Africa have concluded that low soil fertility is more of a production constraint than low water supply (Cissé and Vachaud, 1988; Payne et al, 1990a; Klaij and Vachaud, 1992; van Duivenbooden and Cissé, 1993). Therefore, the effect of plant nutrition on m is of particular interest.…”
Section: The Coefficient Mmentioning
confidence: 99%
See 1 more Smart Citation
“…In moderate VPD environments and for crops with full ground cover (LAI >3-4), estimates of WUE (total aboveground dry mass/seasonal ET) for pearl millet range between 300 and 400 kg ha À1 cm À1 (Chaudhuri and Kanemasu, 1985;Singh et al, 1983), which is comparable to other C4 cereals. However, for traditional low-density, low-input millet crops in areas characterized by high VPD, published estimates of WUE range from as low as 50-150 kg ha À1 cm À1 in unfertilized crops to 150-250 kg ha À1 cm À1 with added fertility (Cisse and Vachaud, 1988;Klaij and Vachaud, 1992;Payne, 1997). In the absence of a full crop cover in traditional low-density millet crops, system ET is poorly related to crop growth; direct soil evaporation in such crops effectively replaces what in a more complete canopy would be transpired water, absorbed from soil surface layers by shallow roots.…”
Section: Water Use Efficiencymentioning
confidence: 99%
“…However, low available soil nutrient supplies affect root as well as canopy growth (Cisse and Vachaud, 1988;Payne et al, 1996) so nutrient scavenging ability may be limited where it is most needed. The rooting pattern of longer-duration African genotypes suggests that they should have the ability to effectively scavenge nutrients present in very low concentrations in the soil, both because of the large soil volume their roots can explore, the long vegetative period they have to do this, and the potential of VAM colonization to enhance nutrient uptake.…”
Section: Nutrient Scavengingmentioning
confidence: 99%